Circular Lead Tanks: A Suggestion - Gáspár, Dorottya (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The question is how we can solve the inconsistency between the following two facts: 1. No baptistery has so far been found in Pannonia. 2. Christians lived in Pannonia at the same time. Upon different analogies (circular lead tanks, church at Zurzach) and examining the rite of the baptism I make hypostatical suggestion: fonts of wood, graves which never contained corpses.